Reliability and validity of the Malay-version Chicago lead knowledge test (CLKT) among parents of preschool children in Malaysia - Mohd Shahrol AW,; Mohd Hasni J,; Zaleha Md Isa, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2021)
The primary objective of this study was to validate the Malay-version Chicago lead knowledge test (CLKT). The CLKT was chosen based on thorough literature review followed by a systematic translation. Data collection involved three phases; initial test was done among 70 parents, retest was done at two weeks apart among similar respondents with response rate of 71.4% (n=50), and another test among 60 professional group. The authors performed non-parametric tests since the data was not normally distributed. The non-parametric test results showed no significant mean knowledge score differences in all demographic parameters. The difficulty factor ranged from 0.01 to 0.99. The mean + SD for difficulty factor was 0.52 + 0.32. Half of the 24 items (n=12) had a difficulty factor of less than 0.75. Only one item (item 6) had item-total correlation of less than 0.2 (0.140). The overall Cronbach’s α coefficient was 0.851. No significant difference was detected by the Wilcoxon Signed-Rank Test between the overall score, the test and retest scores for all domains. All domains showed moderate to strong correlation (Spearman’s Correlation: r=0.546 - 0.814, p<0.001). The Mann-Whitney U test showed a significantly higher knowledge score in professional group compared to parent group for all domains and total knowledge score (p<0.001). The Malay-version CLKT was moderately difficult but had a good reliability and validity. Thus, this instrument can be applied in future larger-scale study.